A STUDY OF OPTICAL AND STRUCTURAL PROPERTIES OF a-Si:H AND a-SiC:H FILMS - Manakov, S.M. (Recent Contributions to Physics, 2011)
Optical and structural properties of amorphous hydrogenated silicon and amorphous silicon carbide films were investigated. The procedure of determination of optical characteristics of films was demonstrated and its effectiveness for homogeneous films was proofed. It was shown, that carbon introduction in an amorphous network resulted not only in increase of optical bandgap, but also in increment of structural deflections in the field of short-range and intermediate-range orders.